SCANNING OF SPARSE ANTENNA ARRAY WITH RANDOM DISTRIBUTION OF RADIATORS AT THE APERTURE - O. A. Yurtsev; I. F. Shalyapin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The main regularities of planar rectangular sparse antenna array with a random radiators distribution at the aperture are analyzed.